Rodinný dům s provozovnou - Balášová, Monika (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Předmětem bakalářské práce je vypracování projektové dokumentace rodinného domu s provozovnou. Objekt je situován na rovinatém pozemku v obci Drásov. Rodinný dům je dvoupodlažní a částečně podsklepený. Hlavní část zastřešení tvoří sedlová střecha s plechovou krytinou, nad částí prvního podlaží a nad provozovnou je vegetační střecha. Svislé konstrukce jsou navrženy ze systému POROTHERM a vodorovné konstrukce tvoří monolitický železobeton. Dům je založen na betonových základových pasech. Výkres byly zpracovány v Archicadu.

The subject of this bachelor thesis is the development of project documentation for a detached house with an office. The building is situated on a flat plot in the village of Drásov. It is a two-storey, partially basemented residential building. The main part of the roof is designed as a pitched roof with metal cladding, while a green roof is used above part of the first floor and above the office space. The vertical load-bearing structures are designed using the POROTHERM masonry system, and the horizontal structures are made of cast-in-place reinforced concrete. The structure is based on concrete strip footings. The drawings were produced in Archicad.
Detached House with an Office
Keywords: rodinný dům; sedlová střecha; vegetační střecha; částečně podsklepený objekt; zděná konstrukce; provozovna; novostavba; detached house; gable roof; green roof; partial basement; brick construction; office; new construction